FACTORS INFLUENCING CONSUMERS SHIFT TOWARDS COLD PRESSED OILS IN GUNTUR, ANDHRA PRADESH: FACTORS INFLUENCING CONSUMERS SHIFT TOWARDS COLD PRESSED OILS IN GUNTUR, A.P. - M. CHARITHA; K. UMA DEVI; M. SATISH RAHUL; B. RAMANA MURTHY (The Journal of Research ANGRAU, 2026)
The study examined the consumer perceptions and factors influencing theconsumers to shift from refined oils to cold pressed oils in Guntur and Tenali towns. A total of 120respondents were interviewed using a structured and pre-tested schedule to ensure accuracyand engagement. The high KMO value and significant Bartlett is a strong justification for factoranalysis. All participants were fully aware of cold-pressed oils but only 20.83 per cent currentlyused them. Health consciousness (70%), taste (41.67%) and traditional processing (35%) emergedas key reasons for preference. Using principal component analysis, nine influencing componentswere extracted, including brand trust, health awareness, social influence and product accessibility,accounting for over 67 per cent of the total variance. The findings aim to reduce the awarenessand adoption gap by generating region-specific insights.